Research on the spatiotemporal characteristics and influence mechanism of the integration of the health industry and tourism industry in the Chengdu-Chongqing economic circle of China - Chen, Xuejun; Deng, Ying (Frontiers in Public Health, 2023)
Given the background of the "Healthy China" strategy and the aging population, the high-quality integration of the health industry and tourism industry is of great significance to meet the national health tourism needs and promote regional coordinated development. Taking the Chengdu-Chongqing economic circle as an example, this paper uses the coupling coordination degree method and geographic detectors to explore the spatiotemporal characteristics and influence mechanism of the integration of the health industry and tourism industry in the Chengdu-Chongqing region. The results show the following: (1) The integration level of the Chengdu-Chongqing economic circle as a whole, four major regional sectors, and 36 cities is relatively low, and the regional differences in the degree of coupling coordination are relatively large, showing a three-level change. Overall, the spatial differentiation characteristics are high in the west and low in the east, radiating from the two nuclei to the periphery. (2) There are obvious regional differences in the spatial connection strength of the integration of the two major industries, which form a radial non-equilibrium structure with the Chengdu and Chongqing main cities as the connection centers. The overall spatial connection network structure is relatively loose, the point-degree centrality has the spatial distribution characteristics of dominated by two poles, led by multiple cores, and weak at the edges, and the division of cohesive subgroups is greatly affected by geographical factors and administrative divisions. (3) The temporal and spatial characteristics of the integration of the two industries are the result of the mutual coupling of market demand, industrial development, policy support, and economic development.